Personalized Feedback Interventions for College Alcohol Misuse: An Update of Walters & Neighbors (2005) - Miller, Mary Beth (Psychol Addict Behav, 2012)
Personalized drinking feedback is an evidence-based and increasingly common way of intervening with high-risk college drinking. This article extends an earlier review by Walters and Neighbors (S. T. Walters & C. Neighbors, 2005, Feedback interventions for college alcohol misuse: What, why, and for whom? Addictive Behaviors, 30, 1168–1182) by reviewing the literature of published studies using personalized feedback as an intervention for heavy drinking among college students. This article updates and extends the original review with a more comprehensive and recent set of 41 studies, most of which were not included in the original article. This article also examines within-subject effect sizes for personalized feedback interventions (PFIs) for high-risk alcohol use and examines the content of PFIs more closely to provide insight on the most essential components that will guide the future development of feedback-based interventions. In general, PFIs appear to be reliably effective at reducing harmful alcohol misuse among college students. Some components are almost universally included (i.e., drinking profile and normative comparison), precluding inferences regarding their unique contribution. Significantly larger effect sizes were observed for interventions that included decisional balance, practical costs, and strategies to limit risks. The present research provides an important empirical foundation for determining the relative contribution of individual components and facets in the efficacy of PFIs.